Respuesta :
To solve a problem like this, you will need to use substitution or elimination. For the sake of an example I will solve this using substitution.
First, solve one of the equations for x or y:
3x-5y=-39
3x=-39+5y
X=(-39+5y)/3
Then substitute for the value of x in the second equation:
6x+2y=-42
6((-39+5y)/3)+2y=-42
Solve for y:
-78+10y +2y=-42
-78+12y=-42
12y=36
Y=3
Once you've solved for y, you can plug in it's value to find x:
X=-39+5(3)/3
X=-24/3
X=-8
So, we can conclude that the correct answer is B. (-8,3)
First, solve one of the equations for x or y:
3x-5y=-39
3x=-39+5y
X=(-39+5y)/3
Then substitute for the value of x in the second equation:
6x+2y=-42
6((-39+5y)/3)+2y=-42
Solve for y:
-78+10y +2y=-42
-78+12y=-42
12y=36
Y=3
Once you've solved for y, you can plug in it's value to find x:
X=-39+5(3)/3
X=-24/3
X=-8
So, we can conclude that the correct answer is B. (-8,3)
B
given the 2 equations
3x - 5y = - 39 → (1)
6x + 2y = - 42 → (2)
multiply (1) by - 2
- 6x + 10 y = 78 → (3)
add (2) and (3) term by term to eliminate x
(6x - 6x) + (2y + 10y ) = (- 42 + 78 )
12y = 36 ( divide both sides by 12 )
y = 3
substitute this value in either of the 2 equations and solve for x
(2) → 6x + 6 = - 42 ( subtract 6 from both sides )
6x = - 48 ( divide both sides by 6 )
x = - 8
solution is (- 8, 3 ) → B